Obese patients and robotic colorectal surgery: systematic review and meta-analysis. Issue 6 (21st September 2020) - Suwa, Y; Joshi, M; Poynter, L; Endo, I; Ashrafian, H; Darzi, A
Abstract: Background: Obesity is a major health problem, demonstrated to double the risk of colorectal cancer. The benefits of robotic colorectal surgery in obese patients remain largely unknown. This meta-analysis evaluated the clinical and pathological outcomes of robotic colorectal surgery in obese and non-obese patients. Methods: MEDLINE, Embase, Global Health, Healthcare Management Information Consortium (HMIC) and Midwives Information and Resources Service (MIDIRS) databases were searched on 1 August 2018 with no language restriction. Meta-analysis was performed according to PRISMA guidelines. Obese patients (BMI 30 kg/m 2 or above) undergoing robotic colorectal cancer resections were compared with non-obese patients. Included outcome measures were: operative outcomes (duration of surgery, conversion to laparotomy, blood loss), postoperative complications, hospital length of stay and pathological outcomes (number of retrieved lymph nodes, positive circumferential resection margins and length of distal margin in rectal surgery). Results: A total of 131 full-text articles were reviewed, of which 12 met the inclusion criteria and were included in the final analysis. There were 3166 non-obese and 1420 obese patients. A longer duration of surgery was documented in obese compared with non-obese patients (weighted mean difference −21·99 (95 per cent c.i. −31·52 to −12·46) min; P < 0·001). Obese patients had a higher rate of conversion to laparotomy than non-obese patients (odds ratio 1·99, 95 per cent c.i. 1·54 to 2·56; P < 0·001). Blood loss, postoperative complications, length of hospital stay and pathological outcomes were not significantly different in obese and non-obese patients. Conclusion: Robotic surgery in obese patients results in a significantly longer duration of surgery and higher conversion rates than in non-obese patients. Further studies should focus on better stratification of the obese population with colorectal disease as candidates for robotic procedures. Graphical Abstract: Obesity is a major health problem that doubles the chance of colorectal cancer. The benefits of robotic surgery for colorectal operations in obese patients versus non-obese patients are unknown. This meta-analysis and systematic review highlights that robotic surgery in obese patients is similar and feasible compared with that in non-obese patients, increasing surgical confidence in its use. CRM, circumferential resection margin. Obesity and colorectal robotic surgery